Factors Associated With Post-traumatic Growth Among Healthcare Workers Who Experienced the Outbreak of MERS Virus in South Korea: A Mixed-Method Study - Hyun, Hye Sun; Kim, Mi Ja; Lee, Jin Hyung (Frontiers in Psychology, 2021)
Background: Infectious disease outbreaks such as COVID-19 and MERS pose a major threat to healthcare workers’ (HCWs) physical and mental health. Studies exploring the positive changes gained from adapting to traumatic events, known as post-traumatic growth (PTG), have attracted much attention. However, it is unclear which factors or experiences lead to PTG among HCWs. The purpose of this mixed-method study was to investigate factors associated with PTG among HCWs who experienced the MERS outbreak in South Korea, and fully describe their experience of developing PTG. Methods: Quantitative data from 78 participants were collected using psychometric tools for Psychological distress, Resilience, and Support for coping, and Post-traumatic growth. Qualitative interviews were conducted with seven nurses. Data were analyzed using the qualitative content analysis method according to the sub-themes of resilience, which was the main factor associated with PTG. Results: We found resilience to have a significant impact on PTG (ß = .486, p =.001). Thus the qualitative interviews were analyzed using the core concepts of resilience. Qualitative interviews with nurses illustrated how participants experienced the development of resilience in terms of its sub-factors: hardiness, persistence, optimism, and support. Conclusion: HCWs who endured the MERS outbreak showed high levels of PTG, and the analysis of the interview data provided a fuller understanding on the experience of remaining resilient and developing PTG. These results provide practical and pragmatic information helpful for developing intervention strategies and protocols that can help HCWs transform adversity into growth and development.